Balancing Profit and Responsibility: The Role of Corporate Social Responsibility in the Digital Era - Karamoy, Tiffany Sayako; Putra Petra Dumgair; Ratna Taliupan; Donald Michi Kassety; Dhian Theresia Kenanga; Wanny Christiana Tumewu (CV. ULIL ALBAB CORP, 2025)
This research aims to explore the application of ethics and corporate social responsibility (CSR) in the context of digital consumerism. In the increasingly evolving digital era, companies are faced with new challenges related to consumer personal data management, algorithm-based marketing, and environmental sustainability. This study uses a quantitative and qualitative descriptive approach, by collecting data through surveys, in-depth interviews, and documentation studies. The results show that although many companies have policies related to personal data management and sustainability, there are still shortcomings in terms of transparency, consumer data protection, and managing the impact of marketing on consumer welfare. In addition, companies also face challenges in reducing the digital divide and minimizing negative impacts on the environment. This research reveals that more consistent CSR and the implementation of more transparent ethical policies can improve a company's reputation, build positive relationships with consumers, and contribute to social and ecological sustainability. In conclusion, companies need to adapt to the increasing demands of ethics and CSR to achieve a balance between financial benefits and social responsibility in the digital age.